3 - Job Vacancy Announcement: Re-Advertisement Position of Executive Secretary - Journal System, (CODESRIA Bulletin, 2025)
The Council for the Development of Social Science Research in Africa (CODESRIA) invites applications from suitably qualiﬁed senior African scholars for the position of Executive Secretary in its pan-African Secretariat located in Dakar, Senegal. This position, which will fall vacant in 2025, is the most senior management post in the Executive Secretariat and the successful candidate will be expected to function as the leader of a team of senior programme staL under the overall supervision of the Executive Committee of the Council.